The plight of the Orang Asli women in Malaysia promoting wild edible plants through street food - Rachel, Thomas T. * (IGI Global, 2021)
In the past, Orang Asli women and men were considered equal, even though their roles were very different. As modernization slowly crept into their lifestyles, the gender divide has gotten a lot bigger and the paternalistic culture has taken a hold of many. Some researchers have said the skewed depictions was influenced by both Christianity and Islam, whereby women were considered to be created by supernatural powers alongside the male species. However, there have been accounts of women being the village chief, but as more anthropologist targeted their research on the Orang asli, the role of a women in the decision making process slowly got relegated.Hence, this review aims to provide the role of Orang Asli women in educating the general public on the usage of wild edibles found in Malaysia and how it could be incorporated into street food to preserve traditional dietary culture. Some of the key challenges, plans and practical applications are discussed to improve rural development and prepare a holistic mediation guideline to buffer the health and safety of the population.